Analysis of the Effect of Exports, Domestic Investment (PMDN), Foreign Investment (PMA) and Labour on Economic Growth in West Nusa Tenggara - Rahmatullah, Raihan; Setiawati, Ririt Iriani Sri (Journal of Regional Economics and Development, 2025)
Over the past five years, West Nusa Tenggara Province (NTB) has been recorded as the region with the lowest economic growth in the Bali and Nusa Tenggara region, particularly in 2019 and 2023. This reflects structural challenges in the regional economy despite efforts to increase investment and foreign trade. This study aims to analyze the effect of Domestic Investment (PMDN), Foreign Investment (PMA), Exports, and Labour on Economic Growth in NTB during the period 2006 to 2023. The data used is annual secondary data from the Central Statistics Agency (BPS) and related agencies. The analysis method used is multiple linear regression with a quantitative approach. The results show that simultaneously, all four variables have a significant effect on NTB's economic growth. However, partially, only the FDI and Labour variables have a positive and significant effect, while DDI and Exports do not show a significant effect. These findings indicate that increasing foreign investment and labour absorption play an important role in driving regional economic growth, while the contribution of PMDN and exports still needs to be improved.